Cross‐sectional Internet‐based survey of Japanese permanent daytime workers' sleep and daily rest periods. Issue 3 (25th May 2018) - Ikeda, Hiroki; Kubo, Tomohide; Sasaki, Takeshi; Liu, Xinxin; Matsuo, Tomoaki; So, Rina; Matsumoto, Shun; Yamauchi, Takashi; Takahashi, Masaya
Abstract : Objectives: This study aimed to describe the sleep quantity, sleep quality, and daily rest periods (DRPs) of Japanese permanent daytime workers. Methods: Information about the usual DRP, sleep quantity, and sleep quality (Japanese version of the Pittsburgh Sleep Quality Index: PSQI‐J) of 3, 867 permanent daytime workers in Japan was gathered through an Internet‐based survey. This information was analyzed and divided into the following eight DRP groups: <10, 10, 11, 12, 13, 14, 15, and 16 h. Results: The sleep durations for workers in the <10, 10, 11, 12, 13, 14, 15, and 16 h DRP groups were found to be 5.3, 5.9, 6.1, 6.3, 6.5, 6.7, 6.7, and 6.9 h, respectively. The trend analysis revealed a significant linear trend as the shorter the DRP, the shorter was the sleep duration. The PSQI‐J scores for the <10, 10, 11, 12, 13, 14, 15, and 16 h DRP groups were 7.1, 6.7, 6.7, 6.3, 6.0 (5.999), 5.6, 5.2, and 5.2, respectively. The trend analysis revealed a significant linear trend as the shorter the DRP, the lower was the sleep quality. Conclusions: This study described sleep quantity, sleep quality, and DRP in Japanese daytime workers. It was found that a shorter DRP was associated with poorer sleep quantity as well as quality.